Free vibration analysis of isotopic rectangular plate with one edge free of support (CSCF and SCFC plate) - Ebirim, Stanley I; Ezeh, J C; Ibearugbulem, M Owus (International Journal of Engineering and Technology, 2014)
The paper presents a theoretical formulation based on Ibearugbulem’s shape function and application of Ritz method. In this study, the free vibration of simply supported plate with one free edge was analyzed. The Ibearugbulem’s shape function derived was substituted into the potential energy functional, which was minimized to obtain the fundamental natural frequency. Aspect ratios from 0.1 to 2.0 with 0.1 increments were considered. The values of fundamental natural frequencies of the first mode were determined for different aspect ratio. For aspect ratio of 1.0, the value of non-dimensional parameter of fundamental natural frequency obtained was 23.86. Comparison was made for values of non-dimensional parameter of fundamental natural frequencies obtained in this study with those of previous research works. It was seen that there is no significant difference between values obtained in this study with those of previous studies.   Keywords: fundamental natural frequency; Ibearugbulem’s shape function; CSCF plate; Ritz method; SCFC plate.